Aristotle / Nicomachean Ethics - Irwin Terence (Hackett Publishing Company, 1985)
This book is a central text in Greek Ethics, a primary source of medieval ethics, and a permanent stimulus to constructive thought about morality. Preface, Introduction, Note on the Text, Abbreviations, Nicomachean Ethics, The Highest Good: Happiness, Virtues of Character in General, The Preconditions of Virtue, The Individual Virtues of Character, Justice, Virtues of Thought, Conditions Connected with Virtue and Vice: Continence and Incontinence, The Varieties of Friendship, Disputes Between Friends with Dissimilar Aims, The Sources of Justification of Friendship, Pleasure, Happiness: Further Discussion, Ethics and Moral Education and Politics, Notes, Annonated Glossary, Aristotle's Literary References, Further Reading.